Predictors of Academic Performance through the Use Of Chatgpt in University Students - Gutiérrez Aguilar, Olger; Delgado-Delgado, Fredy; Meza-Málaga , Joan; Turpo-Gebera, Osbaldo; Ticona Apaza, Fiorela (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The importance that ChatGPT has acquired in the academic world of universities today is critical. The study proposes to validate some predictor variables, such as efficiency in acquiring information, creativity, writing competence, linguistic competence, academic performance, and satisfaction, to generate reliable and valid research instruments. The study was carried out in Peru with a sample of 400 university students of both sexes. Exploratory and confirmatory factor analysis tests were used. For this study, exploratory and confirmatory factor analyses were used. Thus, future research will be able to explore and fully comprehend ChatGPT's utility in various contexts and its impact on higher education.